Пенсійне забезпечення ветеранів війни в Україні - Андрусишин, Ольга Григорівна; Andrusyshyn, Olha Hryhorivna (Національний університет "Львівська політехніка", 2024)
Питання пенсійного забезпечення ветеранів війни є одним з найактуальніших у сучасній Україні, особливо в умовах повномасштабної агресії та збільшення кількості осіб, які отримують статус ветерана. Держава має забезпечити гідний рівень соціального захисту для тих, хто боровся за її незалежність та територіальну цілісність. (Боднар, & Шевченко, 2023). Об’єкт дослідження: система пенсійного забезпечення в Україні. Предмет дослідження: пенсійне забезпечення ветеранів війни в Україні, його законодавче регулювання та практична реалізація. Метою дослідження є комплексний аналіз чинного законодавства та практики пенсійного забезпечення ветеранів війни в Україні, а також розробка пропозицій щодо вдосконалення цієї системи. Результати дослідження: у роботі було виявлено ключові проблеми та виклики, з якими стикаються ветерани війни при реалізації права на пенсійне забезпечення. Запропоновано шляхи оптимізації законодавчої бази та адміністративних процедур для покращення соціального захисту цієї категорії громадян.

The issue of pension provision for war veterans is one of the most urgent in modern Ukraine, especially in conditions of full-scale aggression and an increase in the number of people receiving veteran status. The state must provide a decent level of social protection for those who fought for its independence and territorial integrity. (Bodnar, & Shevchenko, 2023). Object of research: pension provision system in Ukraine. Subject of research: pension provision for war veterans in Ukraine, its legislative regulation and practical implementation. The purpose of the research is a comprehensive analysis of the current legislation and practice of pension provision for war veterans in Ukraine, as well as the development of proposals for improving this system. Research results: the work identified key problems and challenges faced by war veterans in exercising their right to pension benefits. Ways to optimize the legislative framework and administrative procedures to improve social protection for this category of citizens were proposed.
Pension provision for war veterans in Ukraine
Keywords: 6.232.00.00; пенсійне забезпечення; ветерани війни; соціальний захист; державні гарантії; законодавство України; pension benefits; war veterans; social protection; state guarantees; legislation of Ukraine. List of sources used: 1. On the status of war veterans; guarantees of their social protection; (1993). No. 3551-XII. URL: https://zakon.rada.gov.ua/laws/show/3551-12#Text 2. On approval of the Procedure for granting the status of a person with a disability as a result of war to persons who have become disabled as a result of injury; contusion; mutilation or [...]; (2015). No. 685. URL: https://zakon.rada.gov.ua/laws/show/685-2015-%D0%BF#Text 3. Handbook of pension provision for persons discharged from military service; (2024). URL: https://social.mil.gov.ua/wp-content/uploads/2024/03/pensijne-zabezpechennya-vijskovosluzhbovcziv.pdf?20250417